Prediction of Unwanted Crystallization of Freeze-Dried Protein Formulations Using α-Relaxation Measurements - Sebastian Groël; Tim Menzen; Gerhard Winter (MDPI AG, 2023)
There is a lack of methods to predict the isothermal crystallization behavior of amorphous freeze-dried formulations stored below the glass transition temperature. This study applies isothermal microcalorimetry to predict long-term crystallization during product storage time. The relaxation curve of a fresh sample recorded within 12 h after lyophilization is correlated with the long-term crystallization time at the same temperature. Storage conditions of 25 °C and 40 °C are examined and five model formulations containing either sucrose or trehalose with different concentrations of an IgG1 antibody are investigated. The amorphous formulations were created by different freeze-drying processes only differing in their freezing step (random nucleation; additional annealing step of 1.5 h and 3 h, controlled nucleation; quench cooling). Samples that crystallized during the study time of 12 months showed a promising correlation between their relaxation time and crystallization behavior upon storage. Furthermore, the study shows that polysorbate 20 strongly accelerates crystallization of sucrose and that the freezing step itself has a strong impact on the relaxation phenomena that is not levelled out by primary and secondary drying.